The Influence of Parenting Styles on Eating Behavior and Caries in Their Children: A Cross-Sectional Study - María José González-Olmo; Ana Ruiz-Guillén; María Moya-López; Martín Romero-Maroto; María Carrillo-Díaz (MDPI AG, 2022)
The type of parenting style influences the way children cope with problems and can create states of anxiety that can even alter their eating habits, which can cause problems in their oral health. The present study aimed to find out which parenting style is more favorable for the oral health of their children. In this cross-sectional study, 186 children (aged 8-15 years) were examined to assess the mean Decayed/Missing/Filled teeth (DMFT + dmft) index, and they were asked to complete the State-Trait Anxiety Inventory, the Parenting Style Scale, and questions about their oral hygiene habits. On the other hand, their parents answered the Parental Feeding Style Questionnaire and the Children's Eating Behavior Questionnaire. Results showed that a worse oral health status was associated with a higher state of anxiety, more overeating, more emotional eating, and higher psychological control. A higher rate of missing teeth was associated with increased undereating and overeating. Emotional eating was positively related to psychological control. State of anxiety, overeating, and parental psychological control predicted 24.6% of DMFT + dmft. In addition, emotional eating had a moderating effect in DMFT + dfmt only in those with low levels of affection and communication. In conclusion, high psychological control and low levels of parental affection and communication will increase the state of anxiety in children, influencing their caries rate.